The British General Election of 1997 - Butler, David. author. aut Link
XII, 343 p.
Keywords: The most authoritative study of a landmark British General Election - the fifteenth book in the renowned Nuffield series of election studies. This highly readable account covers all the salient features - the background, the campaign, the results and the consequences of Labour's victory. Based on close observation of party headquarters, it explores each party's strategic decisions and their implementation, showing how 1997 saw campaigning techniques at an altogether new level of sophistication. The battle in the media and the constituencies is analysed in detail. There is a mass of data and thorough statistical analysis of the campaign and results. Plates and cartoons entertainingly illustrate the campaign trail and recapture the drama of the election.